Hair Growth Cream Formulation From Shoe Flower Leaf Ethanol Extract (Hibiscus rosa-sinensis L.) As a Hair Grower in Rabbit (Oryctolagus cuniculus) - Munifatul Lailiyah (Sean Institute, 2023)
Hair loss is one of the hair problems that often happens to anyone. hibiscus leaves (Hibiscus rosa-sinensisL.) have traditionally been recognized as having an activity that stimulates hair growth. To make it easier to use, it needs to be made in preparations that are practical and comfortable to use, such as in the form of cream. This study aims to determine the hair growth activity of cream preparations of ethanol extract of hibiscus leaves with concentrations of 10%, 15%, and 20%. In addition, physical quality tests and stability tests of cream preparations were also carried out. Observation of hair activity was carried out by calculating the rate of hair growth in 3 white rabbits. The Stability test was carried out at room temperature storage (25°C ± 2°C). The results of statistical analysis using way ANOVA Repeated measures obtained a significant value of 0.000 (p <0.05). From this significance value, it can be interpreted that there is a significant difference in hair growth activity between all treatment groups. The results showed that hibiscus leaf extract hair growth cream showed hair growth activity the best at a concentration of 20%. The results of the physical quality test of cream at FI had the best characteristics because it produced a physical quality value that was better than FII and FIII. The results of the physical stability test showed that the ethanol extract of hibiscus leaf hair growth cream had good physical stability.